Management of Pustular Psoriasis; The Way Ahead - Shrichand G. Parasramani; Bikash R. Kar; Sushil Tahiliani; Anchala Parthasarathi; Shekhar Neema; Satyaki Ganguly; Dharshini Sathishkumar; K Venkatachalam; Haritha Komeravelli; Jayakar Thomas (Wolters Kluwer Medknow Publications, 2024)
Pustular psoriasis is a specialized variant of psoriasis which can be life threatening if not treated at the earliest. The pathogenesis has been recently linked to the role of interleukin 36. Apart from the corticosteroids, systemic antipsoriatics like acitretin, cyclosporine and methotrexate have been used with some success though unpredictable. With recent identification of role of IL-36 in the pathogenesis of pustular psoriasis, biologics targeting the IL-36 receptors have been used to manage the situation with high degree of success. This narrative review deals with the recent concepts of pathogenesis of pustular psoriasis as well as the current management scenario.